Treatment strategies and outcomes following acute type A aortic dissection repair in patients with bicuspid and tricuspid aortic valves: A meta-analysisCentral MessagePerspective - Tomonari Shimoda, MD; Yujiro Yokoyama, MD; Hisato Takagi, MD, PhD; Toshiki Kuno, MD, PhD; Shinichi Fukuhara, MD (JTCVS Open, 2024)
Background: There is no consensus regarding the strategies for repairing acute type A aortic dissection (ATAAD) in patients with bicuspid aortic valve (BAV). This meta-analysis aimed to compare the treatment strategies and outcomes of ATAAD repair between patients with BAV and those with tricuspid aortic valve (TAV). Methods: A systematic review of databases were performed from inception through March 2023. The primary outcome of interest was all-cause mortality, with a minimum follow-up of 1 year. The secondary outcomes of interest included ratios of performed procedures and rate of distal aortic reoperation. Data were extracted, and pooled analysis was performed using a random-effects model. Results: Eight observational studies including a total of 3701 patients (BAV, n = 349; TAV, n = 3352) were selected for a meta-analysis. Concerning proximal aortic procedures, BAV patients exhibited a higher incidence of necessary root replacement (odds ratio [OR], 6.53; 95% confidence interval [CI], 3.84 to 11.09; P < .01). Regarding distal aortic procedures, extended arch replacement was performed less frequently in BAV patients (OR, 0.69; 95% CI, 0.49 to 0.99; P = .04), whereas hemiarch procedure rates were comparable in the 2 groups. All-cause mortality was lower in the BAV group (hazard ratio, 0.68; 95% CI, 0.50 to 0.92; P = .01). Distal aortic reoperation rates were comparable in the 2 groups. Conclusions: This study highlights distinct procedural patterns in ATAAD patients with BAV and TAV. Despite differing baseline characteristics, BAV patients exhibited superior survival compared to TAV patients, with comparable distal aortic reoperation rates. These findings may be useful for decision making regarding limited versus extended aortic arch repair.